(untitled) (Fiep Bulletin - online, 2012)
The work presented is the result of a project called "Playing and learning holidays: a stroll through the streets of Bethlehem "developed in Unit Municipal Kindergarten Pratinha-Belém-Pará, in the current year, which aimed to create opportunities children’s access to some sights of the city of Bethlehem, promoting learning so enjoyable, cultural and entertaining a proposal inside and outside the educational institution where the child was encouraged to learn their city focusing on culture, leisure and play. The methodology was organized by the cultural languages, musical, bodily-gestural-visual and plastic. As relevant aspects of the situations recorded strengthened by learning several languages, which promoted greater interaction and socializationof children in the findings of the cultural heritage of the city, expressed by the design, creation and movement of the culture acquired and rebuilt by the child. Another relevant aspect was the socialization of knowledge of children with their parents or guardians, in which the acquisition of knowledge was learned and "reinvented" by children, these aspects, significant for children living citizen.